Availability, prices and affordability of essential medicines: A cross-sectional survey in Hanam province, Vietnam - Huong Thi Thanh Nguyen (Public Library of Science (PLoS), 2021)
Objective To measure medicines’ prices, availability, and affordability in Hanam, Vietnam. Methods The standardized methodology developed by the World Health Organization (WHO) and Health Action International was used to survey 30 essential medicines (EMs) in 30 public health facilities and 35 private medicine outlets in 2020. The availability of medicine was computed as the percentage of health facilities in which this medicine was found on the data-collection day. International reference prices (IRPs) from Management Sciences for Health (2015) were used to compute Median Price Ratio (MPR). The affordability of treatments for common diseases was computed as the number of days’ wages of the lowest-paid unskilled government worker needed to purchase medicines prescribed at a standard dose. Statistic analysis was done using R software version 4.1.1. Results The mean availability of originator brands (OBs) and lowest-priced generics (LPGs) was 0.7%, 63.2% in the public sector, and 13.7%, 47.9% in the private sector, respectively. In private medicine outlets, the mean availability of both OBs and LPGs in urban areas was significantly higher than that in rural areas (p = 0.0013 and 0.0306, respectively). In the public sector, LPGs’ prices were nearly equal to their IRPs (median MPRs = 0.95). In the private medicine outlets, OBs were generally sold at 6.24 times their IRPs while this figure for LPGs was 1.65. The affordability of LPGs in both sectors was good for all conditions, with standard treatments costing a day’s wage or less. Conclusion In both sectors, generic medicines were the predominant product type available. The availability of EMs was fairly high but still lower than WHO’s benchmark. A national-scale study should be conducted to provide a comprehensive picture of the availability, prices, and affordability of EMs, thereby helping the government to identify the urgent priorities and improving access to EMs in Vietnam.